How Comparable are Labor Demand Elasticities across Countries? - Fajnzylber, Pablo; Maloney, William F. (World Bank, Washington, DC, 2014)
The authors present the first comparable dynamic panel estimates of labor demand elasticity, using data from Chile, Colombia, and Mexico. They examine the benefits, and limits of the Arellano, and Bond GMM in differences estimator, and the Blundell, and Bond GMM system estimator. They also explore the limitations of such measures for diagnosing flexibility in the labor market. Even accounting for the large variance induced by different estimation techniques, one probably cannot say much about the flexibility of different labor markets based on comparisons of the estimated elasticity of demand. Colombia, for example, which has severe restrictions on firing workers, has much higher long-run wage elasticity than Chile, which has no such restrictions. Three factors make such comparisons difficult: 1) Elasticity differ greatly across industries, so the composition of industry in each country probably affects the aggregate elasticity. Estimates are extremely dependent on the estimation approach, and specification. 2) Even for specific industries, the elasticity of labor demand differs greatly across countries. And the authors find no common pattern of country rankings across industries, which suggests that those differences cannot be attributed solely to systematic characteristics of the countries' labor markets. 3) Estimates for Chile over fifteen years, suggest substantial, and significant variations in elasticity over time. So comparisons across countries depend not only on the industries involved, but also on the sample periods of time used. Estimates change greatly, if not secularly, with sample period.